3
$\begingroup$

In a text I'm reading, an implication is made:

$$\sin\theta-\cos\theta\leq\mu (\cos\theta + \sin\theta) \quad\implies\quad \tan\theta \leq \frac{1+\mu}{1-\mu}$$

I tried using some trigonometric identities to reproduce this result, but it seems I'm not familiar enough with them.

How was this implication made?

$\endgroup$
  • $\begingroup$ It's not always true. What is a condition on $\theta$? $\endgroup$ – Michael Rozenberg Jul 30 at 14:22
  • $\begingroup$ If $\tan\theta \geq 1$ $\endgroup$ – Curl Jul 30 at 14:25
  • $\begingroup$ It's wrong. Try $\theta=\frac{5\pi}{4}$ and $\mu=-\frac{1}{2}.$ $\endgroup$ – Michael Rozenberg Jul 30 at 14:30
2
$\begingroup$

If you divide both sides of the first inequality by $\cos \theta$, you obtain:

$$\frac {\sin \theta - \cos \theta} {\cos \theta} = \tan \theta - 1$$

$$\frac {\mu (\cos \theta + \sin \theta)} {\cos \theta} = \mu ( 1 + \tan \theta)$$

So, assuming $\cos \theta > 0$, from the first inequality you obtain:

$$\tan \theta - 1 \le \mu (1 + \tan \theta) \quad\implies\quad (1 - \mu) \tan \theta \le 1 + \mu$$

Then, assuming $1 - \mu > 0$, you obtain: $$\tan \theta \le \frac {1 + \mu} {1 - \mu}$$

If $\cos \theta < 0$, then by dividing both sides of the first inequality by $\cos \theta$, you must flip the sign. Therefore, the final inequality will be true provided that $1 - \mu < 0$ holds instead.

$\endgroup$
2
$\begingroup$

$$\mu\ge\dfrac{\sin\theta-\cos\theta}{\sin\theta+\cos\theta}$$

$$1+\mu\ge\dfrac{2\sin\theta}{\sin\theta+\cos\theta}$$

$$1-\mu\le\dfrac{2\cos\theta}{\sin\theta+\cos\theta}$$

$$\dfrac{1+\mu}{1-\mu}\ge \tan\theta$$

$\endgroup$
  • $\begingroup$ $\tan\theta=\dfrac{\sin\theta}{\cos\theta}$ $\endgroup$ – J. W. Tanner Jul 30 at 14:19
  • $\begingroup$ for $0 < \sin \theta + \cos \theta$ !! $\endgroup$ – G Cab Jul 30 at 14:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.